Emittance Quality of Terrestrial Digital Multimedia Broadcasting (TDMB) - Sri Arttini Dwi Prasetyowati; Gunawan .; Aries Budiyono (IAES Indonesia Section, 2014)
Television terrestrial broadcasting technology, even fix or mobile have a rapid development along with the development of digital technology. Many countries decided to move from analog TV broadcasting to digital TV broadcasting. Sultan Agung Islamic University (UNISSULA), one of the private university in Central Java had begun to develop the Terrestrial Digital Multimedia Broadcasting (TDMB), as a research to support the migration from analog TV broadcasting to digital TV broadcasting. Because of that goal, must be observed the range of the scope by testing the TDMB Transmitter in UNISSULA. The tool of the test is drive test measurements by Purposive Random Sampling on the three research area, there are, the main road in Semarang, eastern part of the transmitter, Southern part of the transmitter. The Measurement is limited to strength and quality signal.